The effect of good governance mechanism, profitability, and leverage on the timeliness on financial reporting - Merdiana, Siska; Wulandari, Ika (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
Good corporate governance is an important element to attract the attention of investors in investing. Companies that have good governance will realize the vision and mission very seriously. Companies must implement excellent corporate governance; therefore, the author conducted this study to determine how profitability, leverage, and good corporate governance affect the timeliness of financial reporting on the IDX of Manufacturing Companies for the years 2021–2022. Purposive sampling was used for the sampling methodology, and the population comprised 24 companies. Logistic regression was employe as the analysis technique. The discoveries of the review show that a few qualities connected with the review board of trustees significantly affect the practicality of monetary revealing, but different factors, especially those connected with the executives Possession, Productivity, and Influence, have minimal bearing on this issue. The aftereffects of this study have ramifications for organizations that have opened up to the world, asking them to give convenient and far reaching monetary reports that.